IMPROVING THE STUDENTS’ ABILITY TO WRITE DESCRIPTIVE PARAGRAPH THROUGH DRAW LABEL CAPTION (DLC) TECHNIQUE - Ika Sastrawati (Universitas Muhammadiyah Makassar, 2015)
This research aimed at find out the improvement of the students’ writing descriptive paragraph viewed from its content with unity and completeness, language use dealing with tense and preposition through DLC Technique at the eighth grade of MTs.Muhammadiyah Tongko. The technique of this research was a classroom action research (CAR) which was conducted in two cycles in which every cycle consisted of four meetings. The instrument of the research was observation sheet and writing test indicated that the students have high score in writing achievement. The location of this research was taken at the eighth grade of MTs.Muhammadiyah Tongko with a number of the subject were 30 students. The research findings indicated that the application of DLC Technique was significant in improving the students’ writing descriptive paragraph viewed from content and language use. It was proved by the mean score of cycle I was 63.99. It was classified as fair then improved to be 75.50. It was classified as good in cycle II. They are higher than the mean score of diagnostic test namely 50.99 that classified as poor. Therefore there was the improvement of the students’ writing descriptive paragraph viewed from its content with unity and completeness, and language use dealing with tense and preposition.